REFLEKSI KESESUAIAN TEKS DAN KONTEKS: KAJIAN NAFAQAH DALAM KITAB KLASIK “FATHUL MU’IN” - Nurul Rahmawati (Fakultas Syariah (Syari'ah Faculty ), 2015)
In this modern era, Muslims have to face various problems that need to be overcome immediately. One of crucial problems is the emergence of difference perceptions of measurement and kinds of nafaqah: materially and emotionally which are obligations of a husband to fulfil. Other problem is pertaining to when wife deserves to receivenafaqah from her husband. If wife earnsnafaqah for her family because she loves her husband and wants to help him, does wife still deserve the right ofnafaqah?And if husband is not able to earn nafaqah for his family, does wife require her husband’s allowance to leave the house and earn money for daily necessities?. Based on the problems above, the writer tries to analyse nafaqah concept in a classical book:FathulMu’in by Syikh Al-Islam Al-Malibary and its implementation to present life. The concept of nafaqahaccording to FathulMu’in is still relevant to modern life. The implementation of nafaqahconcept according to FathulMu’inis aimed at benefiting both husband and wife. And its implementation should be based on contemporary syari’ah consideration.